Not Running Wild With the CISG - Lookofsky, Joseph (Journal of Law and Commerce, 2011)
In determining the boundaries of supranational legislation some courts adopt an expansionist (dynamic) line. To take a well-known regional example, the European Court of Justice (ECJ) has long been engaged in an exercise in expansionist interpretation, thus broadening the scope of European Union legislation at the expense of the political discretion of EU Member States. Though surely seeking to advance what it sees as the Union’s best interests, the ECJ sometimes “runs amok,” actively extending regional rules in ways that constrain national sovereignty beyond what the Members had originally intended. Or, as one of my Copenhagen colleagues once put it: the ECJ is “running wild.”